Thermal and neutron shielding properties of B-10 containing UV cured hybrid coatings - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2011)
B-10 containing organic-inorganic hybrid coating material based on a UV-curable formulation was prepared via anhydrous sol-gel technique. UV curable coatings were applied on Plexiglas (PMMA) substrates. The molecular structure of the coating material was analyzed by ATR-FTIR spectroscopy technique. The characterization of the UV-curable coating was evaluated by various techniques such as gel content, abrasion resistance, chemical resistance, pencil hardness, pendulum hardness, MEK rubbing test, contact angle, cross-cut test, gloss, transmittance test, neutron absorption, Limiting Oxygen Index and stress-strain tests. Hybrid coatings showed a significant enhancement in radiation shielding properties. The thermal behavior of coatings was also evaluated. It is observed that the thermal stability of coatings mainly depends on their boron and silicate contents. Results of all analysis conducted on hybrid films, and coatings were discussed.
Keywords: Neutron shielding; B-10; UV-curable; PMMA; Protective coating; MECHANICAL-PROPERTIES; CAPTURE THERAPY; BORON; SILICA; NANOCOMPOSITES